020 Post-operative seizure semiology and scalp EEG changes in a case of right temporal lobe epilepsy. Issue 6 (27th May 2022) - Sim, Nicholas Keyi; Singh, Rinki; Maguire, Melissa
Abstract : We report a case of changing semiology of intractable right temporal lobe epilepsy. The patient's semiology of ictal spitting, altered awareness, automatisms and occasional secondary generalization remained stable for many years. 3T MRI head was normal, and subsequent advanced imaging and neu- rophysiology localised the seizure focus to the right temporal lobe and surrounding regions. He received a right temporal lobectomy, with subsequent redo surgery due to incomplete margins. These did not confer seizure freedom. Subsequently his seizure semiology changed to episodic fluent dysphasia with preserved awareness. This was correlated with scalp EEG changes now showing lateralisation to the bilateral temporal lobes. This case demonstrates that seemingly unilateral temporal lobe epilepsy may arise from bilateral networks, which can manifest for years from one hemisphere. It is also possible that extra-temporal origin seizures (for example from perisylvian, fronto-basal or parietal locations) can manifest with temporal-like semiology and can spread to either temporal lobe, and thus can be a cause of epilepsy surgery failure. nchlasim@doctors.org.uk 35